Deficiency of the mitochondrial electron transport chain in muscle does not cause insulin resistance. - Dong-Ho Han; Chad R Hancock; Su Ryun Jung; Kazuhiko Higashida; Sang Hyun Kim; John O Holloszy (PLoS ONE)
Background It has been proposed that muscle insulin resistance in type 2 diabetes is due to a selective decrease in the components of the mitochondrial electron transport chain and results from accumulation of toxic products of incomplete fat oxidation. The purpose of the present study was to test this hypothesis. Methodology/principal findings Rats were made severely iron deficient, by means of an iron-deficient diet. Iron deficiency results in decreases of the iron containing mitochondrial respiratory chain proteins without affecting the enzymes of the fatty acid oxidation pathway. Insulin resistance was induced by feeding iron-deficient and control rats a high fat diet. Skeletal muscle insulin resistance was evaluated by measuring glucose transport activity in soleus muscle strips. Mitochondrial proteins were measured by Western blot. Iron deficiency resulted in a decrease in expression of iron containing proteins of the mitochondrial respiratory chain in muscle. Citrate synthase, a non-iron containing citrate cycle enzyme, and long chain acyl-CoA dehydrogenase (LCAD), used as a marker for the fatty acid oxidation pathway, were unaffected by the iron deficiency. Oleate oxidation by muscle homogenates was increased by high fat feeding and decreased by iron deficiency despite high fat feeding. The high fat diet caused severe insulin resistance of muscle glucose transport. Iron deficiency completely protected against the high fat diet-induced muscle insulin resistance. Conclusions/significance The results of the study argue against the hypothesis that a deficiency of the electron transport chain (ETC), and imbalance between the ETC and β-oxidation pathways, causes muscle insulin resistance.